2022
DOI: 10.3389/fnmol.2022.1001557
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant resting-state functional connectivity and topological properties of the subcortical network in functional dyspepsia patients

Abstract: Functional dyspepsia (FD) is a disorder of gut-brain interaction. Previous studies have demonstrated a wide range of abnormalities in functional brain activity and connectivity patterns in FD. However, the connectivity pattern of the subcortical network (SCN), which is a hub of visceral information transmission and processing, remains unclear in FD patients. The study compared the resting-state functional connectivity (rsFC) and the global and nodal topological properties of SCN between 109 FD patients and 98 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…This schematic structure reflects the network connectivity and offers an integrative approach to explore the communication and transmission of information between regions in the whole brain by investigating the different properties of the cerebral networks, including integration, segregation, centrality, and small-world properties. An increasing number of studies used graph theory to investigate the effects on brain functional networks of several neurological diseases, such as Alzheimer's disease (John et al, 2017), autism spectrum disorder (Chen et al, 2021), schizophrenia (Liu et al, 2016), and functional dyspepsia (Zhang et al, 2022). A recent study reported that patients with cerebral small vessel disease and microbleeds exhibited significantly reduced clustering coefficient, global efficiency, and local efficiency, and an increased shortest-path length, compared to controls and patients with the same disease and no cerebral microbleeds.…”
Section: Introductionmentioning
confidence: 99%
“…This schematic structure reflects the network connectivity and offers an integrative approach to explore the communication and transmission of information between regions in the whole brain by investigating the different properties of the cerebral networks, including integration, segregation, centrality, and small-world properties. An increasing number of studies used graph theory to investigate the effects on brain functional networks of several neurological diseases, such as Alzheimer's disease (John et al, 2017), autism spectrum disorder (Chen et al, 2021), schizophrenia (Liu et al, 2016), and functional dyspepsia (Zhang et al, 2022). A recent study reported that patients with cerebral small vessel disease and microbleeds exhibited significantly reduced clustering coefficient, global efficiency, and local efficiency, and an increased shortest-path length, compared to controls and patients with the same disease and no cerebral microbleeds.…”
Section: Introductionmentioning
confidence: 99%
“…This schematic structure re ects the network connectivity and offers an integrative approach to explore the communication and transmission of information between regions in the whole brain by investigating the different properties of the cerebral networks, including integration, segregation, centrality, and smallworld properties. An increasing number of studies used graph theory to investigate the effects on brain functional networks of several neurological diseases, such as Alzheimer's disease (John et al, 2017), autism spectrum disorder (Chen et al, 2021), schizophrenia (Liu et al, 2016), and functional dyspepsia (Zhang et al, 2022). A recent study reported that patients with cerebral small vessel disease and microbleeds exhibited signi cantly reduced clustering coe cient, global e ciency, and local e ciency, and an increased shortest-path length, compared to controls and patients with the same disease and no cerebral microbleeds.…”
Section: Introductionmentioning
confidence: 99%